REPRESENTASI TRADISI LEFA PADA MASYARAKAT PESISIR DALAM NOVEL LAMAFA KARYA FINCE BATAONA - Swalar, Thomas Krispianus (SINERGI : Jurnal Riset Ilmiah, 2025)
Every society has a culture. The culture and habits are carried out by the community repeatedly. The culture is always passed down to the next generation from generation to generation. Koentjaraningrat (1993) explains that the elements of culture are in the form of language, knowledge, social organization, living equipment and technology, economy, religion, and art. Literature is an expression of human expression in the form of written or oral works based on thoughts, opinions, experiences, and feelings. According to Sumardjo & Saini (1997: 3-4) stated that literature is an expression of human personality in the form of experiences, thoughts, feelings, ideas, enthusiasm, beliefs in a form of Literature is an expression of human expression in the form of written or oral works based on thoughts, opinions, experiences, and feelings. According to Sumardjo & Saini (1997: 3-4) stated that literature is an expression of human personality in the form of experiences, thoughts, feelings, ideas, enthusiasm, beliefs in a form of concrete images that arouse charm with language tools. The Lamafa novel by Fince Bataona is an ethnographic novel that can be seen in the theme, setting, and narrative about the polemic between Lamafa, the name for a stabber in the whale-catching culture in Lamalera with his own brother who wants to conserve whales. The research method used in this study is a qualitative research method, namely research that is descriptive and tends to use process analysis and meaning (subject perspective) is more emphasized.The research data was taken from data sources: Lamafa Novel Quotes that reflect the culture of coastal communities. The data collection techniques used in this study were reading, recording and coding techniques to represent the traditions of coastal communities in the Lamafa novel by Fince Bataona. In addition to these data collection techniques, researchers also conducted interviews with competent sources in the Lefa tradition to obtain data as expected by the researcher and documentation.